The political economy of Land Reform: A new perspective applied to Latin America - Sousa, Miguel Rocha de (2013)
We define in section 1 our notion of land reform, on section 2, the most important social and political movements of land reform in Latin America are presented. On section 3 we use a theoretical model in the context of economic growth with human capital learning-by-doing to evaluate land reforms. Section 4, discusses the results. Section 5 presents some economic efficiency estimates for the “Cédula” project of 2000 in NE Brazil - a market led land bill project, sponsored by the World Bank (WB) and the Ministry of Agricultural Development (MDA). Finally, section 6 concludes, and section 7 presents the references.